Family-centered perinatal services for children with Down syndrome and their families in Florida - Marshall, J; Ramakrishnan, R; Slotnick, A; Tanner, J; Salemi, J; Kirby, R (Elsevier, 2018)
Objective: To examine the experiences of parents or caregivers of children with Down syndrome related to prenatal care, the birth setting, primary and specialty care, and care coordination. Design: Cross-sectional, mixed-methods study. Setting: Florida. Participants: English- or Spanish-speaking parents/primary caregivers (N = 101) of children who were 0 to 18 years old, had a diagnosis of Down syndrome, and were born in Florida. Methods: Participants were identified through snowball sampling and completed an online version of the Family Experiences Survey. Analyses included descriptive statistics, Fisher exact tests, and content analysis of the open-ended questions. Results: Fewer than half of the 101 respondents reported receipt of adequate information after diagnosis of Down syndrome during the prenatal period (n = 18, 19.3%) or in the birth setting (n = 35, 41.2%). Most participants (52.9%–95.4%) reported that they received adequate time and specific information needed and that providers were sensitive to their feelings, values, and family customs during the prenatal period, in the birth setting, and during primary and specialty care. However, fewer than 60% of participants (19.3%–59.1%) recalled that they received information about Down syndrome or helpful programs such as Children’s Medical Services, Early Steps, or Healthy Start either from prenatal care providers or in the birth settings. Conclusion: Our findings highlight the critical role that perinatal care providers play in the establishment of access to and use of specialty care services for neonates with Down syndrome and emphasize the need for family-centered care in prenatal and birth settings.